Analysis of the Financial Performance of the Tangerang City Government and South Tangerang City for the 2019–2024 Fiscal Year Based on Regional Financial Ratios - Shakila Putri Nur Amini; Winwin Yadiati; Ken Paramitha Aryana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the financial performance of the Tangerang City Government and the South Tangerang City Government based on regional financial ratios, including the Regional Financial Independence Ratio (RKKD), the Regional Original Revenue Effectiveness Ratio (PAD), the Regional Financial Efficiency Ratio (REKD), and the PAD Growth Ratio. Tangerang City and South Tangerang City were selected as research objects because they are two cities in Banten Province with high economic activity and are recorded as areas with the highest number of confirmed COVID-19 cases in Banten Province, thus providing a relevant picture of the ability of local governments to maintain their financial performance amidst changing economic conditions. This study uses a qualitative approach. The results show that the Tangerang City Government and the South Tangerang City Government both have a very high level of financial independence with a delegative relationship pattern. However, South Tangerang City shows a higher level of independence because the contribution of PAD to regional income is more dominant. In the PAD Effectiveness Ratio, both regions are included in the very effective category, with South Tangerang City having a slightly higher level of effectiveness than Tangerang City. Meanwhile, the Regional Financial Efficiency Ratio shows that both regions are still in the less efficient to inefficient category, although Tangerang City has a relatively better and more stable level of efficiency. Furthermore, the PAD Growth Ratio indicates that both regions were able to maintain positive PAD growth throughout most of the study period, with South Tangerang City exhibiting a higher growth rate than Tangerang City. Overall, the study results indicate that both local governments have good financial performance in managing regional revenues.